Peranan Jururawat terhadap ibadah solat pesakit: Kajian di Hospital Sultan Abdul Halim, Sungai Petani, Kedah - Luqman Hakim, Muhamad Ghazali (2019)
Prayer is an obligation that must be fulfilled by a Muslim whether in health or illness. Some Muslim patients in the hospital do not perform their prayers because they do not know the rukhsah during their illness. In addition, the nurses' ignorance of prayer rukhsah for their patients has limited their role in helping the patient perform the prayer. This study aimed to examine the level of prayer performance by Muslim patients, assess the role played by nurses in the performance of prayers by Muslim patients and analyze the effectiveness of the role of nurses in the performance of prayers by Muslim patients in Sultan Abdul Halim Hospital, Sungai Petani, Kedah (HSAH). This study used a combination of questionnaires, interviews and observations. The study respondents consisted of 50 nurses randomly selected from Bunga Raya 1 ward, Bunga Raya ward 2, Kenanga ward 5 and Kenanga ward 6. Data from the questionnaire were analyzed descriptively to obtain frequency, percentage and mean values using Statiscal Packages For Social Sciences (SPSS) version 22. Meanwhile, interview and observation data were used to strengthen the questionnaire data to answer the third objective of the study. The findings show that respondents understand prayer rukhsah when they are sick and can provide assistance to the patient and play a role in ensuring that the patient performs the prayer. However, the level of prayer implementation among patients is still at a moderate level. In summary, nurses need to play their part in helping patients to perform prayer worship. This study suggests that HSAH management should raise the level of awareness and role of nurses in ensuring that Muslim patients perform prayers while in hospital ward.